2016
DOI: 10.1007/s00427-016-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

The insect central complex as model for heterochronic brain development—background, concepts, and tools

Abstract: The adult insect brain is composed of neuropils present in most taxa. However, the relative size, shape, and developmental timing differ between species. This diversity of adult insect brain morphology has been extensively described while the genetic mechanisms of brain development are studied predominantly in Drosophila melanogaster. However, it has remained enigmatic what cellular and genetic mechanisms underlie the evolution of neuropil diversity or heterochronic development. In this perspective paper, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 110 publications
(156 reference statements)
2
58
0
Order By: Relevance
“…The GMC is committed to differentiate into a neuron and glial cell. Type II NBs can also selfrenew or can form intermediate neural progenitors (INPs), which give rise to GMCs (Boone and Doe 2008;Homem et al 2015;Altenhein 2015;Koniszewski et al 2016).…”
Section: Embryological Origin Of the Honeybee Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The GMC is committed to differentiate into a neuron and glial cell. Type II NBs can also selfrenew or can form intermediate neural progenitors (INPs), which give rise to GMCs (Boone and Doe 2008;Homem et al 2015;Altenhein 2015;Koniszewski et al 2016).…”
Section: Embryological Origin Of the Honeybee Brainmentioning
confidence: 99%
“…The spatial arrangement, timing of delamination, and molecular network that specifies the NBs are strongly conserved between species (Urbach and Technau 2003;Koniszewski et al 2016). On the other hand, NBs that form specific neuropil structures, such as the MBs, differ between species in number, arrangement, and proliferation behaviour.…”
Section: Embryological Origin Of the Honeybee Brainmentioning
confidence: 99%
“…It has been proposed that the degree to which the insect central complex is elaborated in a given species is correlated with its lifestyle (Strausfeld, 2012; Koniszewski et al, 2016). Developmental studies have revealed that the intricate columnar wiring of the FB is established quite rapidly, but at stages which also vary with the lifestyle of the insect.…”
Section: Introductionmentioning
confidence: 99%
“…The central complex and its related neuropils are highly conserved among insects (Loesel et al, 2002). However, developmental studies addressing these brain compartments are rare (for a recent review, see Koniszewski et al, 2016;Boyan & Reichert, 2011). In hemimetabolan taxa all compartments of the central complex seem to be generated during the embryonic period.…”
Section: Ontogeny and Phylogeny Of The Central Complexmentioning
confidence: 99%